Aggregation Induced Emissive Luminogens for Sensing of Toxic Elements. Issue 7 (8th July 2021) - Zalmi, Geeta A.; Gawade, Vilas K.; Nadimetla, Dinesh N.; Bhosale, Sheshanath V.
Abstract: The major findings in the growing field of aggregation induced emissive (AIE) active materials for the detection of environmental toxic pollutants have been summarized and discussed in this Review article. Owing to the underlying photophysical phenomenon, fluorescent AIE active molecules show more impact on sensing applications. The major focus in current research efforts is on the development of AIE active materials such as TPE based organic fluorescent molecules, metal organic framework, and polymers that can be employed for the detection of toxic pollutants such as CN −, NO2 −, Hg 2+, Cd 2+, As 3+, As 5+, F −, Pb 2+, Sb 3+ ions. Abstract : Ionic challenge ! The major findings in the growing field of aggregation induced emissive (AIE) active materials for the detection of environmental toxic pollutants have been summarized and discussed in this Review article.